Analisis Kelayakan Ekonomi Budidaya Udang Vaname dan Potensi Ekonomi Desa Kaiyasa Kecamatan Oba Utara Kota Tidore Kepulauan - Muhammad, Musdar; Fajri Hatim; Suratno Amiro; Muhammad Kamal (Jurnal Bingkai Ekonomi (JBE), 2024)
The purpose of the study; determine the amount of costs, income and profit of vaname shrimp business feasibility cultivation in kaiyasa village, North Oba sub-district. The data used are secondary and primary data, using descriptive kuntitaf method, the results of research on the potential of land and socio-economic community of kaiyasa village is feasible to do vaname shrimp farming, the results of the feasibility study analysis of vaname shrimp will be profitable and the income of the village community Kaiyasa, for the enlargement of vaname shrimp has a very high demand in the market